2021
DOI: 10.1186/s12889-021-10335-5
|View full text |Cite
|
Sign up to set email alerts
|

The acceptability and feasibility of a pilot study examining the impact of a mobile technology-based intervention informed by behavioral economics to improve HIV knowledge and testing frequency among Latinx sexual minority men and transgender women

Abstract: Background We developed a novel intervention that uses behavioral economics incentives and mobile-health text messages to increase HIV knowledge and testing frequency among Latinx sexual minority men and Latinx transgender women. Here we provide a theoretically-grounded assessment regarding the intervention’s acceptability and feasibility. Methods We conducted 30-min exit interviews with a stratified sample of participants (n = 26 Latinx sexual min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“… 26 , 43 , 51 , 52 , 57 , 58 , 64 , 71 , 76 , 78 , 79 Most studies were implemented after 2000. 20 26 , 34 37 , 39 79 , 81 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 26 , 43 , 51 , 52 , 57 , 58 , 64 , 71 , 76 , 78 , 79 Most studies were implemented after 2000. 20 26 , 34 37 , 39 79 , 81 …”
Section: Resultsmentioning
confidence: 99%
“…Evaluation of acceptability and feasibility was mostly conducted in technology-delivered interventions. 23 , 36 , 38 , 41 , 46 , 47 , 51 , 63 , 70 Participants generally had positive attitudes toward the interventions delivered by website, video or text messages, for example, “I liked the whole goal of the program (Guy2Guy intervention),” and expressed high satisfaction with the program. 38 , 41 , 46 , 51 Mobile app interventions were also shown to be acceptable based on the high System Usability Scale score.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past decade, these tenets of behavioral economics have been increasingly utilized in health care for both patients (cancer screenings [ 14 ], hospital appointment no-show rates [ 7 ], medication adherence for behavioral health [ 15 ], HIV testing rates [ 16 ], obesity and binge eating [ 17 ]) and clinicians (prescribing behavior [ 18 , 19 ], overtreatment of diabetes [ 20 ]), with 83 publications in the top 3 highest impact general medicine journals (Journal of the American Medical Association, The Lancet, The New England Journal of Medicine) from 1998 to 2018 [ 21 ]. A systematic review [ 22 ] found patient portal interventions to be effective in improving a few psychological outcomes, medication adherence, and preventive service use.…”
Section: Introductionmentioning
confidence: 99%